انکار ِحدیث کا تاریخی ارتقاء، محرکات وعوامل کا تنقیدی جائزہ: The Historical Evolution of Hadith Rejection: A Critical Analysis of Its Causes and Motivating Factors - Imran, Ali; Dr. Anwarullah (Al-Amīr Research Journal for Islamic Studies, 2025)
The denial of Hadith has remained a significant and controversial trend in Islamic intellectual history. While the Companions and early generations unanimously recognized Hadith as a primary source of religion alongside the Qur’an, in later periods its authority was questioned under various historical and intellectual influences. Initially, groups such as the Khawarij and the Mu‘tazila rejected certain Hadith due to their rationalist tendencies and preference for reason over transmitted reports. During the Abbasid era, the influx of Greek philosophy, logic, and foreign intellectual currents further strengthened this approach. In colonial South Asia, Hadith rejection emerged as an organized intellectual movement. Thinkers like Sir Syed Ahmad Khan and Ghulam Ahmad Parvez, influenced by Western thought, Orientalist critiques, and modern rationalism, either denied the necessity of Hadith or subordinated it entirely to the Qur’an. A critical examination reveals that the roots of Hadith rejection lie primarily in external intellectual influences and internal scholarly weaknesses, rather than in the authenticity or reliability of Hadith themselves. The classical scholars of Hadith developed rigorous principles of verification, successfully distinguishing between authentic and weak reports, thus providing the Muslim ummah with a reliable corpus. Hadith rejection essentially represents an attempt to undermine one of the two fundamental sources of Islam. Without the Sunnah of the Prophet ﷺ, the Qur’an cannot be fully understood, Shariah cannot be elaborated, and the Islamic system cannot be completed. Hence, the movement of Hadith rejection reflects both intellectual weakness and an effort to destabilize the very foundations of religion. Keywords: Hadith Rejection, Islamic Intellectual History, Rationalism and Modernism in Islam, Qur’an and Sunnah, Orientalist Influence on Islamic Thought